2014
DOI: 10.3233/wor-131727
|View full text |Cite
|
Sign up to set email alerts
|

Policy on manager involvement in work re-integration: Managers' experiences in a Canadian setting

Abstract: BACKGOUND: In Canada and other countries, sickness absence among workers is a significant concern. Local return-to-work policies developed by both management and workers' representatives are preferred to tackle the problem. OBJECTIVE: This article examines how managers perceive this local bipartite agreed upon return-to-work policy, wherein a social constructivist view on the policy process is taken. METHODS: In-depth interviews were held with 10 managers on their experiences with execution of this policy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although believing return-to-work to be a joint responsibility, the supervisors told of spending much time on sick leave follow-up-taking on employees´duties and feeling insecure about how to proceed if they lacked information. Employers/supervisors are recognised as having the central place in the return-to-work process alongside the employee [48]; however, several studies have identified that they struggle with their responsibilities for return-to-work [15,[17][18][19][20]. For instance, employers have been found to perceive accommodation management as a considerable addition to their other duties, feeling ill-prepared, even when given guidance [21].…”
Section: The Burden Of Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although believing return-to-work to be a joint responsibility, the supervisors told of spending much time on sick leave follow-up-taking on employees´duties and feeling insecure about how to proceed if they lacked information. Employers/supervisors are recognised as having the central place in the return-to-work process alongside the employee [48]; however, several studies have identified that they struggle with their responsibilities for return-to-work [15,[17][18][19][20]. For instance, employers have been found to perceive accommodation management as a considerable addition to their other duties, feeling ill-prepared, even when given guidance [21].…”
Section: The Burden Of Responsibilitymentioning
confidence: 99%
“…Several studies have underlined how return-to-work practice is influenced by different perspectives or paradigms of the various stakeholders involved [11,[14][15][16]. This may result in cross-pressure as supervisors attempt to balance workplace interests and employees' health concerns [11,15,17,18]. Several other dilemmas have also been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, various interventions have been made to improve the sickness certification (SC) process [1][2][3][4][5]. In Sweden, as in other countries, there has been a strong focus on collaboration and coordination of stakeholders, in particular to involve the employer in the process [6][7][8][9]. Collaboration between stakeholders such as healthcare professionals, patients, and employers is considered important for a successful return to work (RTW) process for sick-listed patients [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Examples are national legislation (e.g. in the Netherlands, [ 6 ]), regional or local policy (in Canada, [ 7 , 8 ]), or interventions for individual employees. An example of the latter is the workplace intervention by Karlson et al [ 9 , 10 ] to support communication between the employee and the supervisor, which successfully enhanced RTW at 1.5 year follow up for all participants and at 2.5 year follow up (the latter only for younger participants).…”
Section: Introductionmentioning
confidence: 99%